2021
DOI: 10.1155/2021/5185938
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Useful Life Estimation of Aircraft Engines Using a Joint Deep Learning Model Based on TCNN and Transformer

Abstract: The remaining useful life estimation is a key technology in prognostics and health management (PHM) systems for a new generation of aircraft engines. With the increase in massive monitoring data, it brings new opportunities to improve the prediction from the perspective of deep learning. Therefore, we propose a novel joint deep learning architecture that is composed of two main parts: the transformer encoder, which uses scaled dot-product attention to extract dependencies across distances in time series, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…During the downsampling of neighborhood coding, the input resolution of coders could be effectively reduced [37]. Wang et al (2021) [38] proposed a novel joint deep learning architecture, which consisted of two main parts. A transformer encoder that uses scaled dot product attention to extract dependencies across distances in time series.…”
Section: Discussionmentioning
confidence: 99%
“…During the downsampling of neighborhood coding, the input resolution of coders could be effectively reduced [37]. Wang et al (2021) [38] proposed a novel joint deep learning architecture, which consisted of two main parts. A transformer encoder that uses scaled dot product attention to extract dependencies across distances in time series.…”
Section: Discussionmentioning
confidence: 99%
“…The past decade has witnessed the emergence of AI as a practicable tool in clinical management [20]. Preliminary studies have confirmed that AI-aided chest CTs had good sensitivities for detecting COVID-19 lung pathologies [43][44][45]. Sen et al proposed a model to extract features from chest CT images via CNN and then accurately screened out the most significant COVID-19 characteristics-from the patients' chest CT images [46].…”
Section: Discussionmentioning
confidence: 99%
“…The third principle [43,44,45] includes the addition of any form of the attention mechanism to the previously presented approaches. For example, in [43] attention mechanism was used both in the sensor allocation phase and in accounting for the influence of time series position.…”
Section: Novel Sota Approachesmentioning
confidence: 99%